Enhancing a sustainable healthy working life: design of a clustered randomized controlled trial - Koolhaas Wendy; Brouwer Sandra; Groothoff Johan W; van der Klink Jac JL (BMC, 2010)
Abstract Background To improve a sustainable healthy working life, we have developed the intervention 'Staying healthy at work', which endeavours to enhance work participation of employees aged 45 years and older by increasing their problem-solving capacity and stimulating their awareness of their role and responsibility towards a healthy working life. This research study aims to evaluate the process and the effectiveness of the intervention compared with care as usual. Methods/design The study is a cluster-randomized controlled trial design (randomized at the supervisor level), with a 1-year follow-up. Workers aged 45 years and older have been enrolled in the study. Workers in the intervention group are receiving the intervention 'Staying healthy at work'. The main focus of the intervention is to promote a healthy working life of ageing workers by: (1) changing workers awareness and behaviour, by emphasizing their own decisive role in attaining goals; (2) improving the supervisors' ability to support workers in taking the necessary action, by means of enhancing knowledge and competence; and (3) enhancing the use of the human resource professionals and the occupational health tools available within the organization. The supervisors in the intervention group have been trained how to present themselves as a source of support for the worker. Workers in the control group are receiving care as usual; supervisors in the control group have not participated in the training. Measurements have been taken at baseline and will be followed up at 3, 6 and 12 months. The primary outcome measures are vitality, work ability and productivity. The secondary outcomes measures include fatigue, job strain, work attitude, self-efficacy and work engagement. A process evaluation will be conducted at both the supervisor and the worker levels, and satisfaction with the content of the intervention will be assessed. Discussion The intervention 'Staying healthy at work' has the potential to provide evidence-based knowledge of an innovative method to promote a sustainable healthy working life in the older working population. The results of the study will be relevant for workers, employers, occupational health professionals and human resource professionals. Trial registration The trial is registered with the Dutch Trial Register under number NTR2270.